Introdução à Teoria Ergódica - Oliveira, Kaique Micael Moreira de (Universidade Federal de São Carlos, 2023)
This Final Course Paper presents an introduction to Ergodic Theory, focusing on the important Poincaré Recurrence Theorem. Here, the theory necessary for the demonstration of this theorem is developed, starting with an introduction to Measure Theory. Some of the applications of Ergodic Theory are also presented.
Introduction to Ergodic Theory
Keywords: Medida de Lebesgue; Integral de Lebesgue; Princípio de recorrência; Medidas invariantes; Teorema de recorrência de Poincaré; Lebesgue measure; Lebesgue integral; Recurrence principle; Invariant measure; Poincare recurrence theorem; CIENCIAS EXATAS E DA TERRA::MATEMATICA::ANALISE